2015
DOI: 10.1021/la5050283
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ionization on the Behavior of n-Eicosanephosphonic Acid Monolayers at the Air/Water Interface. Experimental Determinations and Molecular Dynamics Simulations

Abstract: Monolayers of n-eicosanephosphonic acid, EPA, were studied using a Langmuir balance and a Brewster angle microscope at different subphase pH values to change the charge of the polar headgroups (Zav) from 0 to -2. Molecular dynamics simulations (MDS) results for |Zav| = 0, 1, and 2 were compared with the experimental ones. EPA monolayers behave as mixtures of mutually miscible species (C20H41-PO3H2, C20H41-PO3H(-), and C20H41-PO3(2-), depending on the subphase pH). The order and compactness of the monolayers de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
(101 reference statements)
0
1
0
Order By: Relevance
“…These semi-soluble species form insoluble monolayers as neutral species but become readily soluble in the solution upon deprotonation. Interfacial acid–base equilibria (apparent surface p K a s) are still widely debated in the literature and often vary from the p K a s of the bulk solution equivalents. , Previous studies of amphiphilic phosphoric and phosphonic acids revealed significant changes in intermolecular interactions and hydration as a result of varying pH. Thus, we utilized surface pressure–area isotherms to study changes in the monolayer phases to gain insight into the noncovalent interactions between molecules. We predicted that these intermolecular interactions will be greatly affected by speciation changes for the tightly packed single-chain species.…”
Section: Introductionmentioning
confidence: 99%
“…These semi-soluble species form insoluble monolayers as neutral species but become readily soluble in the solution upon deprotonation. Interfacial acid–base equilibria (apparent surface p K a s) are still widely debated in the literature and often vary from the p K a s of the bulk solution equivalents. , Previous studies of amphiphilic phosphoric and phosphonic acids revealed significant changes in intermolecular interactions and hydration as a result of varying pH. Thus, we utilized surface pressure–area isotherms to study changes in the monolayer phases to gain insight into the noncovalent interactions between molecules. We predicted that these intermolecular interactions will be greatly affected by speciation changes for the tightly packed single-chain species.…”
Section: Introductionmentioning
confidence: 99%